Recent Progress in Red Blood Cells-Derived Particles as Novel Bioinspired Drug Delivery Systems: Challenges and Strategies for Clinical Translation - Vincy, Antony; Mazumder, Sarmistha; Amrita,; Banerjee, Indranil; Hwang, Kuo Chu; Vankayala, Raviraj (Frontiers in Chemistry, 2022)
Red Blood Cells (RBCs)-derived particles are an emerging group of novel drug delivery systems. The natural attributes of RBCs make them potential candidates for use as a drug carrier or nanoparticle camouflaging material as they are innately biocompatible. RBCs have been studied for multiple decades in drug delivery applications but their evolution in the clinical arena are considerably slower. They have been garnering attention for the unique capability of conserving their membrane proteins post fabrication that help them to stay non-immunogenic in the biological environment prolonging their circulation time and improving therapeutic efficiency. In this review, we discuss about the synthesis, significance, and various biomedical applications of the above-mentioned classes of engineered RBCs. This article is focused on the current state of clinical translation and the analysis of the hindrances associated with the transition from lab to clinic applications.